Chromosome-level genome assembly of the intertidal lucinid clam Indoaustriella scarlatoi - Yang Guo; Zhaoshan Zhong; Nannan Zhang; Minxiao Wang; Chaolun Li (Scientific Data)
Abstract Lucinidae, renowned as the most diverse chemosymbiotic invertebrate group, functions as a sulfide cleaner in coastal ecosystems and is thus ecologically important. Despite their significance, genomic studies on these organisms have been limited. Here, we present the chromosome-level genome assembly of Indoaustriella scarlatoi, an intertidal lucinid clam. Employing both short and long reads, and Hi-C sequencing, we assembled a 1.58 Gb genome comprising 690 contigs with a contig N50 length of 9.00 Mb, which were anchored to 17 chromosomes. The genome exhibits a high completeness of 95.4%, as assessed by the BUSCO analysis. Transposable elements account for 56.02% of the genome, with long terminal repeat retrotransposons (LTR, 42.66%) being the most abundant. We identified 34,469 protein-coding genes, 74.43% of which were functionally annotated. This high-quality genome assembly serves as a valuable resource for further studies on the evolutionary and ecological aspects of chemosymbiotic bivalves.